Integration of sol-gel frequency agile materials for tunable RF devices - Fragkiadakis, Charalampos (Cranfield University, 2012)
This thesis focuses on the use of high permittivity tunable dielectrics and more specifically sol-gel ferroelectric thin films for low cost, high performance tunable devices such as varactors and filters at RF and microwave frequencies. The topics covered include measurement techniques for the characterization of tunable dielectrics at low and microwave frequencies, fabrication processes, electrical and acoustic modeling of thin film ferroelectric varactors, performance optimization using conductive electrodes, realization of tunable microwave circuits and integration of tunable dielectrics with conventional bulk acoustic wave resonators (FBAR). Cont/d.